Bilirubin dosage in cord blood: could it predict neonatal hyperbilirubinemia? - Adélia Jeha Nasser Bernaldo (São Paulo Medical Journal)
CONTEXT: With early discharge, many newborns have to be readmitted to hospital for hyperbilirubinemia to be treated, and this has been held responsible for the reappearance of kernicterus. OBJECTIVE: To evaluate whether bilirubin levels in cord blood could predict neonatal hyperbilirubinemia that would require treatment, in full-term newborns up to their third day of life. TYPE OF STUDY: Prospective study. SETTING: Neonatal Unit of Hospital Israelita Albert Einstein, São Paulo, Brazil. PARTICIPANTS: 380 full-term newborns considered normal: with or without ABO/Rh blood group incompatibility and without other complications. PROCEDURES: Blood was taken from the umbilical cord for analysis of conjugated, unconjugated and total bilirubin serum levels. The newborns were followed up until discharge, and unconjugated bilirubin that required phototherapy was compared to the cord bilirubin assay. Discriminant analysis was used to classify newborns: with or without risk of needing phototherapy by the third day of life. MAIN MEASUREMENTS: Bilirubin assay in cord blood; mother's and newborn's blood groups; phototherapy indication. RESULTS: The mean value for unconjugated bilirubin in cord blood was significantly higher in newborns whose unconjugated bilirubin required phototherapy. The presence of ABO blood group incompatibility was a significant variable in relation to unconjugated bilirubin that required phototherapy. The most useful cutoff point for unconjugated bilirubin in cord blood was 2.0 mg/100 ml. DISCUSSION: Cord blood could be collected, stored and used for further analysis of unconjugated bilirubin levels as a means for considering whether or not to discharge a moderately jaundiced child from hospital, in association with other resources. CONCLUSIONS: Blood incompatibility between mother and child was a predictor for the appearance of hyperbilirubinemia that required treatment. Considering a cutoff point of 2.0 mg/100 ml, it could be concluded that 53% of the newborns who had greater unconjugated bilirubin levels in cord blood would reach levels requiring phototherapy by the third day of life.